Amplitude calibration with the HiSCORE-9 array. (July 2015) - Epimakhov, S; Brückner, M; Budnev, N; Bogorodskii, D; Chvalaev, O; Dyachok, A; Gress, O; Horns, D; Ivanova, A; Kiruhin, S; Konstantinov, E; Korosteleva, E; et al.
Abstract: HiSCORE is a non-imaging wide-angle Cherenkov array for the detection of extensive air showers induced by ultrahigh energy gamma-rays above 10 TeV and cosmic ray studies above 100 TeV. In October 2013 a 9-station engineering array has been deployed in Tunka valley. For HiSCORE-9, two DAQ systems are being used. The second system is a DRS4 based acquisition system with WhiteRabbit integrated time synchronization. We present the first results on the amplitude calibration from the data of this DAQ system.